Agama, tradisi dan kesenian dalam manuskrip La Galigo - Nurhayati Rahman, (Universiti Kebangsaan Malaysia, 2008)
The La Galigo manuscript is the priceless inheritance for Buginese. It includes of four aspects as its essence. They are religion, sacred book, tradition and art, Before Islam came, Buginese believed La Galigo as a view of life whorshiping the highest God namely Patotoqé who stays in Botting langiq and also Dewi Sinauq Toja who stays in Buri Liu. This faith has spawn ceremonies and traditions that persist in Buginese culture until nowadays. The guardian and savior of La Galigo are Bissu and Sanro. If Bissu is a transvestite priest who has a duty to connect human life to the god, then Sanro is a behind-the screen practitioner who provides all the equipment needed for the ceremony. Almost in every human traditional ceremony, including harveting of grain and entering a new house, Sanro and Bissu are there. This shows La Galigo has strong connection with religion, tradition and art. It also reflects the complexity of the traditional art. There is an inner power which involves spirit of the owner. Thus, those people who want to perform the sacred art beyond the context without considering the sanctity and feeling of the owners wouldl loose the aura of art and what remains is an unspirit creativity